Vatican diplomacy, ecclesiastical jurisdiction, and border disputes: a frustrated apostolic vicariate and the incipient Chileanization of Tacna and Arica (1892-1910) (Quinto Sol, 2025)
Drawing on documents from the Vatican Apostolic Archive and on reports by priests connected in various ways to the diplomatic controversy over the definition of sovereignty of the provinces of Tacna and Arica (1894–1929) between Peru and Chile, this article examines the efforts of Chilean diplomacy before the Holy See to establish an apostolic vicariate in the region in the early twentieth century. It argues that Chile sought to detach these territories from the ecclesiastical jurisdiction of the Peruvian diocese of Arequipa as part of a broader strategy for the Chileanization of the area. In response, the Holy See, adhering to the international law in force at the time, sought to prevent the religious sphere from being politically instrumentalized by the parties in conflict. It also proposed alternatives to address the pastoral needs of the inhabitants without inflaming nationalist passions. In doing so, it aimed to protect Catholic interests and the relations between the Church and the states involved. When the vicariate project failed to advance, Chilean authorities adopted more drastic measures against Peruvian priests in the region and sought to legitimize the presence of Chilean clergy, ensuring their cooperation with the area’s nationalization process.
Keywords: Holy See; international dispute; diplomacy; mediation